Best Practices in Specialized Amyloidosis Centers in the United States: A Survey of Cardiologists, Nurses, Patients, and Patient Advocates. Issue 15 (May 2021) - Nativi-Nicolau, Jose; Sarswat, Nitasha; Fajardo, Johana; Finkel, Muriel; Abdulsattar, Younos; Castaño, Adam; Klein, Lori; Haddad-Angulo, Alexandra
Background: Because transthyretin amyloid cardiomyopathy (ATTR-CM) poses unique diagnostic and therapeutic challenges, referral of patients with known or suspected disease to specialized amyloidosis centers is recommended. These centers have developed strategic practices to provide multidisciplinary comprehensive care, but their best practices have not yet been well studied as a group. Methods: A qualitative survey was conducted by telephone/email from October 2019 to February 2020 among eligible healthcare providers with experience in the management of ATTR-CM at US amyloidosis centers, patients with ATTR-CM treated at amyloidosis centers, and patient advocates from amyloidosis patient support groups. Results: Fifteen cardiologists and 9 nurse practitioners/nurses from 15 selected amyloidosis centers participated in the survey, with 16 patients and 4 patient advocates. Among participating healthcare providers, the most frequently cited center best practices were diagnostic capability, multidisciplinary care, and time spent on patient care; the greatest challenges involved coordination of patient care. Patients described the "ideal" amyloidosis program as one that provides physicians with expertise in ATTR-CM, sufficient time with patients, comprehensive patient care, and opportunities to participate in research/clinical trials. The majority of centers host patient support group meetings, and patient advocacy groups provide support for centers with physician/patient education and research. Conclusions: Amyloidosis centers offer comprehensive care based on staff expertise in ATTR-CM, a multidisciplinary approach, advanced diagnostics, and time dedicated to patient care and education. Raising awareness of amyloidosis centers' best practices among healthcare providers can reinforce the benefits of early referral and comprehensive care for patients with ATTR-CM.